2022
DOI: 10.5194/acp-22-14075-2022
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence characteristics, absorption properties, and radiative effects of water-soluble organic carbon in seasonal snow across northeastern China

Abstract: Abstract. Water-soluble organic carbon (WSOC) in the cryosphere can significantly influence the global carbon cycle and radiation budget. However, WSOC in the snowpack has received little scientific attention to date. This study reports the fluorescence characteristics, absorption properties, and radiative effects of WSOC based on 34 snow samples collected from sites in northeastern China. A significant degree of regional WSOC variability is found, with concentrations ranging from 0.5±0.2 to 5.7±3.7 µg g−1 (av… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 129 publications
(168 reference statements)
3
4
0
Order By: Relevance
“…Niu et al. (2022) reported that a PARAFAC component in snow samples, similar to our L‐HULIS, substantially contributes to the light absorption of WSOC at UV wavelengths.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Niu et al. (2022) reported that a PARAFAC component in snow samples, similar to our L‐HULIS, substantially contributes to the light absorption of WSOC at UV wavelengths.…”
Section: Resultssupporting
confidence: 82%
“…Therefore, it is reasonable to speculate that this portion of secondary BrC, as identified by L-HULIS, may potentially represent these strong BrC chromophores. Niu et al (2022) reported that a PARAFAC component in snow samples, similar to our L-HULIS, substantially contributes to the light absorption of WSOC at UV wavelengths.…”
Section: Examination Of Secondary Source Of Brc Determined By L-hulissupporting
confidence: 58%
See 1 more Smart Citation
“…Radiative effect induced by CAs is approximately twice that of massequivalent sulfate aerosol (Liu et al 2022). Further, the interactions between CAs and radiation can effectively disturb atmospheric stratification and circulation by heating atmosphere (Ding et al 2016), and accelerate glacier and snow melting due to darkening effect (Pu et al 2021, Niu et al 2022. In ATAL, atmospheric warming induced by CAs causes increased precipitation over Asia through strengthening the monsoon Hadley circulation (Fadnavis et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…WSOC can reach approximately 27–83% of the organic carbon mass of aerosols (Yu et al 2004 and references therein) and is primarily emitted from combustion of biomass and fossil fuels, or secondarily formed from oxidation of VOCs, aromatic compounds, and high molecular weight hydrocarbons with anthropogenic or biogenic origin (Du et al, 2014 ; Park et al, 2015 ). WSOC affect the formation and physical properties of clouds, Earth’s radiative balance, and atmospheric chemistry with implications for regional and global climate change (Duarte et al, 2015 , 2019 ; Niu et al 2022 ; Tang et al, 2020 ). Moreover, due to their toxicity, particle-bound WSOC has been associated with human cardio-respiratory diseases (Cheung et al 2009 ; Ramgolam et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%